2013
DOI: 10.1371/journal.pone.0083359
|View full text |Cite|
|
Sign up to set email alerts
|

Peg3 Mutational Effects on Reproduction and Placenta-Specific Gene Families

Abstract: Peg3 (paternally expressed gene 3) is an imprinted gene encoding a DNA-binding protein. This gene plays important roles in controlling fetal growth rates and nurturing behaviors. In the current study, a new mutant mouse model has been generated to further characterize the functions of this DNA-binding protein. Besides known phenotypes, this new mutant model also revealed potential roles of Peg3 in mammalian reproduction. Female heterozygotes produce a much smaller number of mature oocytes than the wild-type li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(129 citation statements)
references
References 37 publications
12
115
1
1
Order By: Relevance
“…Second, we used a mutant model targeting the Peg3 locus as a negative control. 12 In this knockout (KO) model, transcription of Peg3 was truncated by 2 poly(A) signals inserted into intron 5 as part of an expression cassette; thus, the PEG3 protein is depleted in these cells (Fig. 1A).…”
Section: Identification Of the Downstream Genes Of Peg3 In Mef Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we used a mutant model targeting the Peg3 locus as a negative control. 12 In this knockout (KO) model, transcription of Peg3 was truncated by 2 poly(A) signals inserted into intron 5 as part of an expression cassette; thus, the PEG3 protein is depleted in these cells (Fig. 1A).…”
Section: Identification Of the Downstream Genes Of Peg3 In Mef Cellsmentioning
confidence: 99%
“…11 This possibility has been further supported by the observation that many placenta-specific gene families associated with H3K9me3 modification are de-repressed in mutant embryos lacking PEG3. 12 Although premature at the moment, a series of these recent studies suggested that PEG3 was a transcriptional repressor for its downstream genes through H3K9me3-mediated mechanisms. 11,12 As an ongoing effort, in the current study we performed a new series of ChIP-seq experiments using mouse embryonic fibroblast (MEF) cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the Peg3 floxed allele features the 6 th exon flanked by 2 loxP sites and thus is excised upon Cre-mediated recombination. 15,16 The PEG3 protein cannot be translated from the modified ORF of Peg3 del6 due to a frame shift and subsequent nonsense mutation. Therefore, when the recombined allele (Peg3 del6 ) is paternally transmitted, the result is the abrogation of PEG3 protein due to the introduced mutation on the paternal allele and the silencing of the maternal allele by genomic imprinting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two publically available mouse strains, B6.129-Kras tm4Tyj /Nci (LSL-Kras G12D ) and STOCK Tg (MMTV-Cre)4Mam/J (MMTV-Cre), were purchased from Jackson Laboratories. 13,14,15 The third strain, Peg3 floxed , was generated in the lab. 16,17 The order of breeding was carried out as follows: first, the Peg3 floxed allele was bred with the LSL-Kras G12D model to generate double heterozygous mice.…”
Section: Methodsmentioning
confidence: 99%